Vulvar cancer: pathogenetic types, diagnosis, treatment, plastic operations - V. G. Cherenkov; I. V. Aleksandrova; A. A. Shpenkova (Опухоли женской репродуктивной системы, 2014)
The morbidity rates and pathogenetic types of vulvar cancer (VC) and reasons for its advance were studied in the Novgorod Region. The condylomatous type of VC (that has developed in the presence of vulvar intraepithelial neoplasia) was stated in 18% of patients; 48 (75%) had a classical pathogenetic type 2 of VC (caused by significant vulvar dystrophy and lichen sclerosus). The tumor process had an intermediate variant in 9.4% of patients with VC. The reason for untimely diagnosis is that obstetricians and gynecologists have no current knowledge of vulvar carcinogenesis, the standards for the diagnosis and treatment of vulvar dystrophies. Tumor cryodevitalization and the application of a radio-wave knife create optimal conditions for implementing the basic principles of ablastics and antiblastics. Reparative surgery using skin and fascial flaps from the posterior surface of the hip to close the organ-tissue defect resulting from vulvectomy, to reduce the risk for postoperative complications, and to form the appearance of the organ is the method of choice in treating VC.